2017
DOI: 10.15632/jtam-pl.55.4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of the aluminum alloy AW5005 behavior subjected to tension and perforation under dynamic loading

Abstract: The paper describes mechanical behavior of aluminum alloy AW5005 (EN AW5005) under impact loading. The work is focused on tensile tests and the process of perforation of aluminum alloy AW5005 sheets. Experimental, analytical and numerical investigations are carried out to analyse in details the perforation process. Based on these approaches, ballistic properties of the structure impacted by a conical nose shape projectile are studied. Different failure criteria are discussed, coupling numerical and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Similarly, El-Magd and Abouridouane demonstrated that the ductility of AA7075 increased with the increasing strain rate [19]. Bendara et al analysed the mechanical behaviour of the AW 5005 (AA5005) aluminium alloy under impact loading [20]. They conducted tensile tests for a wide range of strain rates and a perforation test.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, El-Magd and Abouridouane demonstrated that the ductility of AA7075 increased with the increasing strain rate [19]. Bendara et al analysed the mechanical behaviour of the AW 5005 (AA5005) aluminium alloy under impact loading [20]. They conducted tensile tests for a wide range of strain rates and a perforation test.…”
Section: Introductionmentioning
confidence: 99%
“…The process is assumed to be adiabatic due to the reduced time for heat transmission out of the generation zone. Taylor-Quinney coefficient (β), the percentage of plastic work converted into heat, is assumed to be equal to 0.9 [24][25][26]. The increase of temperature is given in Equation 5depending also on the density of the material (ρ) and the specific heat at constant pressure (C p ).…”
Section: Mechanical Behavior Of Inconel 718mentioning
confidence: 99%
“…A more sophisticated approach to define failure, i.e. damage initiation deformation ε , has been recently developed in [19]. Two functions with four constants H, I, J and K are determined using an optimization method.…”
Section: Proposed Constitutive Relationmentioning
confidence: 99%